2012
DOI: 10.1007/s12185-012-1179-6
|View full text |Cite
|
Sign up to set email alerts
|

A tetraploid minimally differentiated acute myeloblastic leukemia with extensive erythrophagocytosis: a case report and literature review

Abstract: Tetraploidy is a rare chromosome number aberration in de novo acute myeloid leukemia (AML), and may be associated with erythrophagocytosis by leukemic blast cells. We report a 48-year-old female patient with minimally differentiated acute myeloblastic leukemia (AML-M0) exhibiting tetraploidy and erythrophagocytosis. The karyotype was 46,XX[2]/92,XXXX[18]. Bone marrow aspirate smears showed large and prominent nuclei, with erythrophagocytosis in leukemic cells. Fluorescence in situ hybridization using RUNX1 dua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
2
8
0
Order By: Relevance
“…Other features, such as cytoplasmic vacuoles, irregular nuclear contour/nuclear budding, and background myelodysplasia, observed in a subset of patients, also have been described by others [2,6,7,10]. Erythrophagocytosis, described in several cases previously [26,27,23], was not an obvious finding in this study. Cytoplasmic inclusions, observed in 14 cases in this cohort, were reported by one earlier study [2].…”
Section: Discussionsupporting
confidence: 84%
“…Other features, such as cytoplasmic vacuoles, irregular nuclear contour/nuclear budding, and background myelodysplasia, observed in a subset of patients, also have been described by others [2,6,7,10]. Erythrophagocytosis, described in several cases previously [26,27,23], was not an obvious finding in this study. Cytoplasmic inclusions, observed in 14 cases in this cohort, were reported by one earlier study [2].…”
Section: Discussionsupporting
confidence: 84%
“…The abnormality is rare and described in 0.98-1.2% of all AML patients. [4][5][6] Until date, less than 70 cases have been described in the literature. [6,7] Our finding is consistent with the low frequency of near tetraploidy/tetraploidy in AML.…”
Section: Discussionmentioning
confidence: 99%
“…A global defect in cell cycle control may lead to endoreduplication or nuclear mitotic division, but the exact mechanism is not yet known. [6] Near tetraploidy has been reported to be associated with different morphological French-American-British subtypes of AML and with large bizarre blasts. [4,5,7] Although DNA content was not evaluated in the present case, Kwong and Wong (1995) demonstrated that in hyperdiploid myeloid leukemias, increase in DNA content is accompanied by a corresponding increase in blast size.…”
Section: Discussionmentioning
confidence: 99%
“…A bone marrow study performed in late February showed no persistent leukemic blasts or myelodysplasia. A CR was achieved morphologically; however, a chromosomal analysis of the marrow cells showed 46,XY,del(20)(q12q13) [14]/46,XY [6] (Table). Clonal hematopoiesis was considered to exist without myelodysplastic changes.…”
Section: Case Reportmentioning
confidence: 99%
“…Near-tetraploidy/tetraploidy (NT/T)-AML has been reported to occur preferentially in elderly male patients and is morphologically characterized by very large blasts (2,3). Some cases have been reported to be associated with extensive erythrophagocytosis by leukemic blasts (4)(5)(6). Cases of NT/T-AML generally show a dismal prognosis, and the median overall survival (OS) is reported to be 5-9 months (1-3).…”
Section: Introductionmentioning
confidence: 99%